SISTEM PENGONTROLAN KEMUDI DAN FESS PADA MOBIL PENGGUNA KURSI RODA - Cinta aulia; mifta hunaya; Aan Febriansyah; Indra Dwisaputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Persons with disabilities are a handful of people with special needs who have the same roles and rights as society in general. However, they will usually find it difficult to carry out daily activities, for example in using a vehicle. Therefore we designed a Car Control System for Wheelchair Users to help people with disabilities, especially for those who experience physical limitations in one of the bodies, namely the legs. The Steering Control System and FESS that we designed use a Brushless DC Motor as the main driver of the steering system using a microcontroller in the form of Arduino and the Brushless DC Motor Controller itself. As well as the existence of a Tilt sensor or tilt sensor which is useful as a signal to Arduino to activate the Flywheel with the aim of having a charging system from the remaining rotation of the Flywheel as energy savings. The method we use is retrieval of RPM data from 1.2V – 3.3V so that we get a stable RPM value.